2013
DOI: 10.1152/japplphysiol.00010.2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single- or multifrequency bioelectrical impedance analysis and spectroscopy for assessment of appendicular skeletal muscle in the elderly

Abstract: Bioelectrical impedance analysis (BIA) is used to assess skeletal muscle mass, although its application in the elderly has not been fully established. Several BIA modalities are available: single-frequency BIA (SFBIA), multifrequency BIA (MFBIA), and bioelectrical impedance spectroscopy (BIS). The aim of this study was to examine the difference between SFBIA, MFBIA, and BIS for assessment of appendicular skeletal muscle strength in the elderly. A total of 405 elderly (74.2 ± 5.0 yr) individuals were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…Bioelectrical impendence spectroscopy represents an advance from BIA as it is able to distinguish between extra and intracellular water. This may explain why initial studies suggest that bioelectrical impendence spectroscopy demonstrates better correlation to muscle function tests than BIA (17). At present, DXA is the most widely used method to assess lean mass (as a surrogate for muscle mass) in research studies.…”
Section: Methods Of Measuring Muscle Size Strength and Physical Permentioning
confidence: 99%
“…Bioelectrical impendence spectroscopy represents an advance from BIA as it is able to distinguish between extra and intracellular water. This may explain why initial studies suggest that bioelectrical impendence spectroscopy demonstrates better correlation to muscle function tests than BIA (17). At present, DXA is the most widely used method to assess lean mass (as a surrogate for muscle mass) in research studies.…”
Section: Methods Of Measuring Muscle Size Strength and Physical Permentioning
confidence: 99%
“…5 The cut off point by using BIA was defined by ASMI. The result was obtained through a comparison between total SMM and height squared.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that for body composition, multifrequency devices provide greater reliability when measuring body composition [37] . Similarly, equations derived from one population may not be readily applicable to a different population [38] .…”
Section: Discussionmentioning
confidence: 99%